Head to the field: Fieldwork as a direct experience learning tool in the integrated geography course - Lidya Lestari Sitohang,; Bambang Hariyanto,; Aida Kurniawati,; Sukma Perdana Prasetya,; Eko Budiyanto,; Nugroho Hari Purnomo, (Technium Social Sciences Journal, 2023)
This article explores the researchers’ use of fieldwork as a direct experience learning tool in an integrated geography course as a precursor of spatial courses offered in the upcoming semester. The researchers analysed the students' direct experience learning process in the field, guided by the research questions (a) what are the supporting aspects of the fieldwork course during the integrated geography course, and (b) what are the constraining aspects of the fieldwork course in relation to the achievement of course learning by students in their second year. The findings indicate that students found the fieldwork to be worthwhile but had concerns about the time spent on preparation and the study workload. The students were able to make important connections to the course content. Nevertheless, the students are also considerate of the insufficient lecturer’s guidance, nature attraction, peer disturbance, and assignment workloads as the constraining elements in their learning process.